2002
DOI: 10.1182/blood.v99.6.2114
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 inhibits tumor cell growth by means of a T-cell–dependent mechanism

Abstract: IntroductionInterleukin-17 (IL-17), originally identified by Rouvier et al 1 as cytolytic T-lymphocyte (CTL)-associated antigen 8, is a T-cellderived cytokine with homology to Herpesvirus saimiri. [1][2] It is expressed mainly by activated CD4 ϩ CD45RO ϩ memory T cells. [3][4] CD4 T cells can be classified into T-helper (Th) 1 cells, which secrete interferon (IFN) ␥, IL-2, and tumor necrosis factor (TNF) ␤; Th2 cells, which produce IL-4, IL-5, IL-6, IL-10, and IL-13; and Th0 cells, a common precursor with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
247
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(263 citation statements)
references
References 49 publications
10
247
0
6
Order By: Relevance
“…Conflicting data have been reported regarding the capacity of IL-23 and IL-17 to favour or inhibit cancer growth (Benchetrit et al, 2002;Langowski et al, 2006;Numasaki et al, 2003). We found that the overall expression of the genes encoding these factors is weak in prostate specimens, but nevertheless similar in BPH and PCA (Steiner et al, 2003).…”
Section: Discussionmentioning
confidence: 76%
“…Conflicting data have been reported regarding the capacity of IL-23 and IL-17 to favour or inhibit cancer growth (Benchetrit et al, 2002;Langowski et al, 2006;Numasaki et al, 2003). We found that the overall expression of the genes encoding these factors is weak in prostate specimens, but nevertheless similar in BPH and PCA (Steiner et al, 2003).…”
Section: Discussionmentioning
confidence: 76%
“…Inhibitory titers correspond to the serum dilution that reduces the induced IL-6 secretion by 50%. When indicated, supernatant of the J558L cell line transfected with a cDNA encoding mIL-17A was used as a source of natural glycosylated IL-17A (a kind gift of Dr E. Tartour, Paris, France) [36].…”
Section: Assesment Of Anti-il-17 Inhibitory Ab In Vitromentioning
confidence: 99%
“…18 -23 In previous studies, we have demonstrated that human tumors transfected with IL-17 showed increased growth in nude mice, whereas immunogenic tumors were inhibited in immunocompetent mice by means of a T-cell-dependent mechanism. 12,24 In all these studies, IL-17 was not naturally produced by the tumors but overexpressed secondary to the transfection of cells. In order to address the relevance of these models in tumors spontaneously occurring in humans, we look for the natural expression of IL-17 in mycosis fungoides (MF) and Sezary syndrome (SS), which are primary epidermotropic cutaneous T-cell lymphomas (CTCL).…”
mentioning
confidence: 99%